Generate and situated transformation as a paradigm for models of computational creativity. Issue 3 (2nd October 2017) - Kelly, Nick; Gero, John S.
Abstract: This paper describes 'generate and situated transformation' as a paradigm for models of computational creativity that can lead to novel questions and methods of enquiry. It describes the need for systems that can move towards a frame within which a design solution can be found. The term situated transformation is defined, with reference to Boden's notion of transformation and ideas from situated cognition, as a change of frame that is based upon experience. The paper then provides a demonstration of simple systems with generate and situated transformation that embody this idea. It then elaborates upon these models showing parallels within established systems in the literature. The paper concludes with a discussion of research questions and avenues of enquiry that are apparent within this paradigm.